Business Continuity: Toward to the Holding Company of BUMDes in Buleleng Regency - Trisnawati, Ni Luh De Erik; Kartika, Riana Dewi; Kasih, Ni Luh Sri (International Journal of Social Science and Business, 2021)
Business management based on the local culture of catur purusa artha by making dharma (truth) the basis for carrying out all its activities, creating internal conditions in the form of a conducive work climate. This study aims to examine the application of the value of catur purusa artha and product innovation in creating business continuity. The research population is all active BUMDes in Buleleng Regency. Sampling in this study using random sampling technique in order to obtain as many as 92 observational data. The data analysis technique used in this study was the Component based SEM, Partial Least Square (PLS) analysis method. The results showed that the value of Catur purusa artha had a significant effect on product innovation. Product innovation has a significant effect on business continuity and the value of catur purusa artha affects business continuity through product innovation.